Current approaches to periprocedural anticoagulation treatment in patients undergoing atrial fibrillation ablation - N. Z. Gasymova; E. N. Mikhailov (Российский кардиологический журнал, 2019)
Catheter ablation is a standard treatment for patient with symptomatic and drugrefractory atrial fibrillation. As for every invasive approach, ablation is associated with certain risk of complications. About 2-3% of adverse events are related to hemorrhage or thromboembolism. Therefore, periprocedural anticoagulation scheme is of paramount importance to minimize the risk of both types of complications. Here we describe the factors, associated with thromboembolic and bleeding risks, and the evolving approaches for periprocedural anticoagulation treatment. Special attention is paid to uninterrupted oral anticoagulation and potential role of reverse agent in management of procedure-related hemorrhages.